Studi Pendahuluan Pengembangan Lembar Kerja Peserta Didik Berbasis Environmental Sustainability - Nugraheni, Zahra; Hadi, Sofwan; Pratiwi, Mega Melinda Ayu (Wacana Akademika: Majalah Ilmiah Kependidikan, 2025)
Climate change poses a global threat to the sustainability of life. Cultivating environmental awareness is urgently needed. Mathematics education plays a strategic role in achieving sustainable development goals. This qualitative research aims to gather initial information on the need to develop student worksheets based on environmental sustainability on the topic of data presentation. The research stages include: initial-final analysis, analysis of student characteristics, task analysis, concept analysis, and formulation of specific learning objectives. Data were collected through observation, interviews, and documentation. Data were analyzed using Miles and Huberman's qualitative analysis. The results of the study indicate that: (1) teachers have not fully integrated the environmental context, either directly or through media, so that the meaning of mathematics learning is relatively low; (2) students' environmental awareness and numeracy literacy skills in the context of the topic of data presentation are still low. These findings form the basis for developing student worksheets.